The relationship between leg muscle power and dribbling skills among futsal players - Rosyida Aprilia Wulandari; Ni Komang Ayu Juni Antari; Made Hendra Satria Nugraha; Ni Luh Putu Gita Karunia Saraswati (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Futsal is a sport that involves using the feet to manipulate the ball and score as many goals as possible to reach the opponent's goal. It is crucial to have a strong command of basic techniques, including proficient dribbling skills. Dribbling talent is essential to getting past opponents' control and creating goal-scoring opportunities. The higher a player's skill in dribbling the ball, the greater his chances of winning. This study aimed to determine the potential correlation between leg muscle power and ball dribbling skills in futsal players. Methods: This study used observational analytical methods with a cross-sectional approach. Consecutive sampling was the technique used for the sampling process. This research was carried out from September to December 2023 at My Stadium Futsal Arena. A total of 89 people were recruited to participate in this study. In data collection, participants' leg muscle power was measured using a vertical jump test, and their dribbling skills were assessed using a dribbling test. Results: There was a significant relationship between leg muscle power and dribbling skills in futsal players. The higher the leg muscle power value, the better futsal players' dribbling skills. Conclusion: The findings indicated a correlation between leg muscle power and ball dribbling skills in futsal players.